2021
DOI: 10.1002/pc.25961
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wood thermal modification on the supermolecular structure of polypropylene composites

Abstract: The thermal modification of wood can be an interesting way of improving adhesion in polymer composites, although the mechanical properties of composites with heat treated wood presented so far in many works arouse much controversy. In this work, effects of thermal modification of wood on the supermolecular structure and morphology of wood/polypropylene composites (WPC) were investigated using X-ray diffraction, hot stage optical microscopy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the X c value for WPC FNT was 23.4%, while the addition of heat-treated WFs to the PLA matrix increased the X c value in the range of 34.0–43.9%, with the use of WFs treated at greater treatment times resulting in higher values. Odalanowska and Borysiak [ 32 ] reported that a significant increase in nucleation activity of the WF surface was estimated in WPCs with WF after heat treatment in the temperature range of 160–180 °C. This is due to thermal degradation of the most unstable chemical composition in this temperature range, such as hemicelluloses.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the X c value for WPC FNT was 23.4%, while the addition of heat-treated WFs to the PLA matrix increased the X c value in the range of 34.0–43.9%, with the use of WFs treated at greater treatment times resulting in higher values. Odalanowska and Borysiak [ 32 ] reported that a significant increase in nucleation activity of the WF surface was estimated in WPCs with WF after heat treatment in the temperature range of 160–180 °C. This is due to thermal degradation of the most unstable chemical composition in this temperature range, such as hemicelluloses.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Numerous studies have focused on improving the interfacial adhesion between PP polymer and wood substrates, which can be achieved by modifying the adhesives used by the addition of appropriate ternary compatibilizers. [8][9][10] In addition, the activation of the PP polymer can be improved by plasma treatment, [11] chlorination, [12] and isocyanate silane grafting, [13] while deligninfication, [14] heat treatment, [15] and enzyme treatment [16] of the wood substrates have been aimed at the reduction of the polarity of the wood. These methods are effective, but another modification processing step needs to be applied prior to the surface decoration.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are mainly two ways to improve the properties of WPC. One way is modification of wood fillers via chemical or physical treatments, such as alkali treatment [10], esterification [12], amino acid treatment [13] and heat treatment [14]. However, these treatments have evident disadvantages including the use of toxic compounds, complex processing steps and significant increase in manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%